The lost - Patterson, James, 1947-; Raymond, Emily, 1972- (2014)
"Magical teen siblings Whit and Wisty Allgood struggle against a mounting public opposition to magic and a brutal crime wave led by a powerful wizard intent on ruling the City"--
Keywords: Brothers and sisters -- Fiction; Witches -- Fiction; Wizards -- Fiction; Totalitarianism -- Fiction; Government, Resistance to -- Fiction; Magic -- Fiction; Brothers and sisters -- Juvenile fiction; Witches -- Juvenile fiction; Wizards -- Juvenile fiction; Totalitarianism -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Magic -- Juvenile fiction; Young adult fiction